Construction of an intelligent maintenance system of intensive broadband service - Chao CAI; Lin YUAN; Xina ZHANG (Dianxin kexue)
With the spreading of broadband acceleration strategy and the quick development of streaming media such as IPTV/OTT,a higher quality of experience on the services of telecom operators need to be satisfied.The current maintenance system and method is operating on different levels and segments,which is lack of interactive functions and cooperation.Therefore,a new method is required to satisfy the network maintenance work in the new developing environment.A new method was proposed to construct the intelligent maintenance system of the intensive broadband service.With this method,it is able to achieve the end-to-end quality monitoring and automatic self-diagnosis functions.The method will benefit the services of telecom operators and will improve the efficiency and intelligence of telecom operators.